Shuddering Attacks - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The pathophysiology of shuddering attacks in 4 infants, ages 8 to 14 months, was studied using video-electroencephalographic monitoring, at the Epilepsy Center, Nishi-Niigata Central National Hospital, Niigata, Japan.